MORBIDITY AND MORTALITY PROFILE OF NEONATES ADMITTED IN NEONATAL INTENSIVE CARE UNIT IN A TERTIARY CARE HOSPITAL, SOUTH-EASTERN RAJASTHAN, JHALAWAR MEDICAL COLLEGE, JHALAWAR: A RETROSPECTIVE STUDY - MEENA, NARESH KUMAR; PUNIA, HARISH; SHARMA, AKANSHA; MEENA, NIDHI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to study the morbidity and mortality patterns in a special newborn care unit (SNCU)/neonatal intensive care unit (NICU) of a tertiary care teaching hospital. Methods: A retrospective study was carried out in the SNCU/NICU of Jhalawar Medical College, Jhalawar. The duration of the study was 3 years. A retrospective case record review and analysis was done. Secondary data collected from the online SNCU Software (National Health mission Government of India). Results: Eight thousand seven hundred and forty-eight neonates were admitted in NICU. 2488 (59.9%) were male and 1657 (40.1%) were female, 4047 (46.3%) were normal birth babies, and 4701 (53.7%) were low birth weight babies. According to the outcome, total 6753 (77.19%) were discharged successfully, 1464 (16.66%) died, 382 (4.36%) were referred, and 149 (1.7%) were leave against medical advice. Birth asphyxia was the most common morbidity 2404 (27.36%) followed by neonatal sepsis (18.06%) and neonatal jaundice (15.44%). Birth asphyxia were more in inborn unit (p<0.0001). Sepsis is more prevalent in out born unit (p<0.0001). Hypoxic ischemic encephalopathy/moderate-to-severe birth asphyxia was the most common cause of death (28.23%), followed by neonatal sepsis (20.62%) and respiratory distress syndrome (19.35%), and major congenital malformations were cause of death in 106 (7.24%). Mortality due to neonatal sepsis was significantly high in outborn unit (p<0.0001). Conclusion: Birth asphyxia, neonatal sepsis, and respiratory distress syndrome were the leading causes of mortality in this study. These leading causes of mortality in the study could be prevented by adequate training of nursing staff and doctors, timely referral to tertiary care if required.